2015
DOI: 10.1128/jvi.00462-15
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Influenza A Virus Infection: Tools To Track Infection and Limit Tropism

Abstract: Influenza A viruses display a broad cellular tropism within the respiratory tracts of mammalian hosts. Uncovering the relationship between tropism and virus immunity, pathogenesis, and transmission will be critical for the development of therapeutic interventions. Here we discuss recent developments of several recombinant strains of influenza A virus. These viruses have inserted reporters to track tropism, microRNA target sites to restrict tropism, or barcodes to assess transmission dynamics, expanding our und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Recombinant viruses expressing fluorescent proteins have been generated to monitor viral replication, including DNA (e.g., Vaccinia virus (Diallo et al, 2011;Dominguez et al, 1998) and human cytomegalovirus (Marschall et al, 2000)), and double-stranded (e.g., HIV (Daelemans et al, 2005)), positive-stranded (e.g., murine hepatitis virus (Freeman et al, 2014)), negative-stranded segmented e.g., arenaviruses (Ortiz-Riano et al, 2013), and nonsegmented (e.g., Newcastle disease virus (Vigil et al, 2007) and Ebola virus (Towner et al, 2005)) RNA viruses. These recombinant systems are powerful tools to monitor viral infections in real time (Fiege and Langlois, 2015;Fukuyama et al, 2015;Manicassamy et al, 2010), to evaluate antivirals (Nogales et al, 2014a;Towner et al, 2005), and to identify NAb (Baker et al, 2015b;Nogales et al, 2014a;Rimmelzwaan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant viruses expressing fluorescent proteins have been generated to monitor viral replication, including DNA (e.g., Vaccinia virus (Diallo et al, 2011;Dominguez et al, 1998) and human cytomegalovirus (Marschall et al, 2000)), and double-stranded (e.g., HIV (Daelemans et al, 2005)), positive-stranded (e.g., murine hepatitis virus (Freeman et al, 2014)), negative-stranded segmented e.g., arenaviruses (Ortiz-Riano et al, 2013), and nonsegmented (e.g., Newcastle disease virus (Vigil et al, 2007) and Ebola virus (Towner et al, 2005)) RNA viruses. These recombinant systems are powerful tools to monitor viral infections in real time (Fiege and Langlois, 2015;Fukuyama et al, 2015;Manicassamy et al, 2010), to evaluate antivirals (Nogales et al, 2014a;Towner et al, 2005), and to identify NAb (Baker et al, 2015b;Nogales et al, 2014a;Rimmelzwaan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…With the development of reverse genetics techniques, similar approaches have been implemented for the generation and characterization of replication-competent fluorescentexpressing IAVs (Avilov et al, 2012;Baker et al, 2015b;Fiege and Langlois, 2015;Fukuyama et al, 2015;Manicassamy et al, 2010;Nogales et al, 2015Nogales et al, , 2014aReuther et al, 2015;Rimmelzwaan et al, 2011). However, similar methods have not been used for the generation of recombinant fluorescent-expressing IBVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, fusing of miR‐192 target sequence into IAV genome could attenuate influenza pathogenicity in mice . Furthermore, the ability of miRNA‐based attenuation method to determine virus fitness through introducing various number and location of target sites is superiority over classical viral attenuation methods . Together, these evidences suggested that the engineering flu genome virus containing the target sites of deregulated miRNAs in a species‐specific manner could be employed as a high‐throughput strategy which is able to provide a new class of flu IAV vaccines.…”
Section: Microrna and Exosome‐based Vaccinementioning
confidence: 99%
“…Despite the importance of this virus, far less is known about IBV relative to influenza A virus (IAV). Research into IAV has been greatly enhanced by several replication-competent reporter viruses (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). These reporter viruses have been crucial for identifying host factors, understanding basic viral pathogenesis, screening for antiviral compounds, and characterizing broadly reactive antibodies (6)(7)(8)(9)(10)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%